After the Berlin Wall : memory and the making of the new Germany, 1989 to the present - Harrison, Hope Millard (Cambridge ; New York, NY : Cambridge University Press, 2019)
"Thirty years after the fall of the Berlin Wall on November 9, 1989, people around the world still remember the joyous drama of that night and the days and nights that followed. Even at a time before smartphones and twitter helped people experience an event together, the surprise opening of the Berlin Wall was viewed by millions on television sets and splashed across headlines around the globe. For Berliners and Germans themselves, dramatic days followed which would change their lives and their country"--
Introduction: The Berlin Wall and German historical memory -- Divergent approaches to the fall of the Wall -- The fight over memory at Bernauer Strasse -- Creating a Berlin Wall memorial ensemble at Bernauer Strasse -- Remembering the Wall at Checkpoint Charlie -- The Berlin senate's master plan for remembering the Wall -- The federal government and the Berlin Wall -- Victims and perpetrators -- Conflicting narratives about the Wall -- Heroes to celebrate and a new founding myth -- Conclusion: Memory as warning
Includes bibliographical references and index
Description based on print version record
UCLA Library - CDL shared resource.
Keywords: Berlin Wall, Berlin, Germany, 1961-1989 -- Historiography; Collective memory -- Germany; International relations; National characteristics, German; Germany -- History -- Unification, 1990 -- Historiography; Germany -- Politics and government -- 1990-; History